Depression in systemic lupus erythematosus: Modifiable or inheritable? a two-sample mendelian randomization study - Chen, Jinyun; Xu, Ting; Wu, Min (Frontiers in Genetics, 2022)
Observational studies have found increased incidence of depression, the leading cause of disability worldwide, in patients with systemic lupus erythematosus (SLE). However, it’s not clear whether the association was genetically inheritable or caused by modifiable risk factors, such as socioeconomic factors. We investigated the causal relationship between genetically predicted SLE and depression by two-sample Mendelian randomization analysis. Single nucleotide polymorphisms (SNPs) associated with SLE were selected as instrumental variables (IVs) from a genome-wide association study (GWAS) of 14,267 European-ancestry participants. A large GWAS of depression (180,866 European-ancestry participants) and another GWAS of major depressive disorder (MDD) (173,005 European-ancestry participants) were selected as outcomes. Then we estimated the effects of IVs on the odds of depression or MDD by using the inverse-variance weighted (IVW) meta-analysis method (random-effects), which had a power of 90% to detect 4% increase of depression in SLE. Interestingly, genetically predicted SLE decreased the odds of depression (odds ratio (OR): 0.995; 95% CI: 0.990–0.999; p= 0.025) and MDD (odds ratio (OR): 0.985; 95% CI: 0.975–0.996; p= 0.009), indicating increased depression in SLE was not due to inheritable risk factors.